Fifth Five Year Plan 1974-79 Second Year's Programme 1975-76 - Planning Commission (Planning Commission, 1974)
This publication presents the revised estimate for expenditure under plan schemes for the year 1974-75 and also the details of the annual plan Programme for 1975-76. the outlay provided for 1975-76 in the State sector is Rs. 90.50 crores. A provision at Rs. 10.20 crores has been included tor implementation of Centrally Sponsored and Central Sector Schemes. Thus the gross plan outlay for 1975-76 is Rs. 100.70 crores.
Statements and Brief Description of Programmes